STRENGTHENING CHARACTER WITH INTEGRATION OF PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) IN LESSONS AT MAN MATARAM CITY - Luthfi, Zainul; Taufik, H. M; Hakim, Lukman; Arifin, Bustanul (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
in Mataram City with learning design, implementation, evaluation and results of learning effectiveness. The study used a descriptive qualitative approach. The results showed a learning design with Habituation; communication that respects children; development of children's talents and independence; good role models; discipline; according to technical instructions and the Pancasila Student Profile. Character Material Pancasila Student Profile, soft skill development, freedom of critical thinking. Implementation is carried out with Habituation: Tadarrus Al-Qur'an, congregational dhuha prayer, congregational zuhur prayer, applying the habit of smiling, greeting, greeting, being polite, and being polite. Identification of student needs, clear learning objectives, research on learning materials, being an example (role model). Differentiation, Problem based learning, Student-centered, hands-on practice, Integration of materials with the Pancasila Student Profile, project-based learning, collaborative learning, simulation, case studies, group work, discussion, teacher role models, Pancasila Student Profile character culture, intracurricular, extracurricular and co-curricular integration, strengthening literacy and information technology media. The evaluation results show strengthening of the character of Devotion to God Almighty, and noble character, global diversity, mutual cooperation, creativity, critical thinking, independence, responsibility. Freedom, Participation (Caring), creativity, tolerance, Pancasila Student Profile character. The conclusion shows the effectiveness of strengthening character through learning design, learning implementation, and evaluation.